Transient ischemic dilation as a diagnostic marker in myocardial perfusion SPECT protocols: a systematic review and meta-analysis - Nasim Namiranian; Mahmood Emami; Aryan Naghedi; Seid Kazem Razavi-Ratki (The Indonesian Heart Association, 2020)
Abstract Background: Transient ischemic dilation (TID) measures left ventricle (LV) volume changes which can be associated with combination of myocardial and endocardial ischemia. Various stress methods, single photon emission computerized tomography (SPECT) imaging protocol, camera and software incite controversy on TID cut off. The purpose of this study was to evaluate the TID ratio in detection of coronary artery disease (CAD) categories in a systematic review and meta-analysis. Method: We conducted a systematic search of electronic databases (PubMed, Scopus, Embase and Web of Science) up to 1 January 2017. The reference lists of all included studies were searched for a higher accuracy. The search strategy was according a defined PICO as P: none, I: Transient ischemic dilation, O: Coronary Artery Diseases, C: Angiographies. Statistical analysis was done by Comprehensive meta-analysis software version 2 (CMA-2). Result: After study selection process, 7 studies were selected for data extraction. TID was studied from 1987. The sample size of included studies ranged between 86 and 545. The mean age of included patients varied between 58 and 69 years old. Ranges of TID in CAD categories were excluded. The pooled estimates of TID in single and dual pharmacological stress test in three CAD categories were calculated. Conclusion: Our findings show that more studies are needed to compare the TID variability. Although in this study meta-analysis was done and TID was summarized from studies but the software differences were ignored.